Multifunctional "core-shell" nanoparticles-based gene delivery for treatment of aggressive melanoma. (December 2016) - Li, Ling; Song, Linjiang; Yang, Xi; Li, Xia; Wu, Yuzhe; He, Tao; Wang, Ning; Yang, Suleixin; Zeng, Yan; Yang, Li; Wu, Qinjie; Wei, Yuquan; et al.
Abstract: Gene therapy may be a promising and powerful strategy for cancer treatment, but efficient targeted gene delivery i n vivo has so far remained challenging. Here, we developed a well-tailored and versatile "core-shell" ternary system (RRPHC) of systemic gene delivery for treatment of aggressive melanoma. The capsid-like "shell" of this system was engineered to mediate depth penetration to tissues, simultaneously target the CD44 receptors and integrin αv β3 receptors overexpressed on neovasculature and most malignant tumor cells, while the "core" was responsible for nucleus-targeting and effective transfection. The RRPHC ternary complexes enhanced cellular uptake via dual receptor-mediated endocytosis, improved the endosomal escape and significantly promoted the plasmid penetration into the nucleus. Notably, RRPHC ternary complexes exhibited ultra-high gene transfection efficiency (∼100% in B16F10 cells), which surpassed that of commercial transfection agents, PEI 25K, Lipofectamine 2000 and even Lipofectamine 3000. Especially, RRPHC ternary complexes showed excellent serum resistance and remained high gene transfection efficacy (∼100%) even in medium containing 30% serum. In vivo biodistribution imaging demonstrated RRPHC ternary complexes possessed much more accumulation and extensive distribution throughout tumor regions while minimal location in other organs. Furthermore, systemic delivery of the pro-apoptotic mTRAIL gene to tumor xenografts by RRPHC ternary complexes resulted in remarkable inhibition of melanoma, with no systemic toxicity. These results demonstrated that the designed novel RRPHC ternary complexes might be a promising gene delivery system for targeted cancer therapy in vivo .